Time Zero for Net Zero: A Coal Mine Baseline for Decarbonising Heat - Alison A. Monaghan; Luke Bateson; Adrian J. Boyce; Neil M. Burnside; Rebecca Chambers; Julia R. de Rezende; Eilidh Dunnet; Paul A. Everett; Stuart M. V. Gilfillan; Muhammad S. Jibrin; Gareth Johnson; Richard Luckett; et al. (Earth Science, Systems and Society)
Mine water geothermal energy could provide sustainable heating, cooling and storage to assist in the decarbonisation of heat and achieving Net Zero carbon emissions. However, mined environments are highly complex and we currently lack the understanding to confidently enable a widespread, cost-effective deployment of the technology. Extensive and repeated use of the mined subsurface as a thermal source/store and the optimisation of operational infrastructure encompasses a range of scientific and technical challenges that require broad partnerships to address. We present emerging results of a pioneering multidisciplinary collaboration formed around an at-scale mine water geothermal research infrastructure in Glasgow, United Kingdom. Focused on a mined, urban environment, a range of approaches have been applied to both characterise the environmental change before geothermal activities to generate “time zero” datasets, and to develop novel monitoring tools for cost-effective and environmentally-sound geothermal operations. Time zero soil chemistry, ground gas, surface water and groundwater characterisation, together with ground motion and seismic monitoring, document ongoing seasonal and temporal variability that can be considered typical of a post-industrial, urban environment underlain by abandoned, flooded coal mine workings. In addition, over 550 water, rock and gas samples collected during borehole drilling and testing underwent diverse geochemical, isotopic and microbiological analysis. Initial results indicate a connected subsurface with modern groundwater, and resolve distinctive chemical, organic carbon and stable isotope signatures from different horizons that offer promise as a basis for monitoring methods. Biogeochemical interactions of sulphur, carbon and iron, plus indications of microbially-mediated mineral oxidation/reduction reactions require further investigation for long term operation. Integration of the wide array of time zero observations and understanding of coupled subsurface processes has significant potential to inform development of efficient and resilient geothermal infrastructure and to inform the design of fit-for-purpose monitoring approaches in the quest towards meeting Net Zero targets.